Turkish Islam on its home ground - Sherwood, Robert (The Middle East, 1987)
The survey of Islamic fundamentalism in Turkey argues that the recent force of religious sentiment is deeply rooted among the rural population - and especially among Turkey's Kurdish population. The situation in Diyarbakir is described in some detail. The relationship between religious and national sentiment is also discussed. (DÜI-Asd)